A first-principles study of NbSe2 monolayer as anode materials for rechargeable lithium-ion and sodium-ion batteries. (17th May 2017) - Lv, Xingshuai; Wei, Wei; Sun, Qilong; Huang, Baibiao; Dai, Ying
Abstract: There is a great desire to search for suitable anodes with good performance for rechargeable metal-ion batteries, which require not only large capacity but excellent rate performance and cycling stability. In this work, the electronic properties of NbSe2 monolayer were explored based on first-principles calculations. We performed a full geometry optimization for Li/Na-adsorbed structures and obtained favorable adsorption sites. The metallic character for both pristine NbSe2 monolayer and the Li/Na-adsorbed NbSe2 ensures good electrical conduction. In addition, we find that NbSe2 monolayer is more inclined to adsorb Li and Na atoms with smaller adsorption energy under Li/Na-rich condition, indicating the superiority of NbSe2 monolayer as an electrode. Then, we obtained a relatively low diffusion barrier of approximately 0.205 eV for Li and, in particular, a significantly small diffusion barrier of about 0.086 eV for Na, which ensures excellent cycling performance of NbSe2 monolayer as a battery electrode. Most importantly, the Li and Na adsorption density in NbSe2 monolayer can be as high as Li2 NbSe2 and Na4 NbSe2, corresponding to theoretical specific capacities of 203 and 312 mAh·g −1, respectively. And the average electrode potentials were predicted to be 0.51 V for the chemical stoichiometry of Li2 NbSe2 and 0.22 V for Na4 NbSe2 . In view of these excellent properties, our work predicts that NbSe2 monolayer can be a promising anode material for the development of low-cost high-performance Li- and Na-ion batteries.